WORKSHOP INOVASI PROGRAM PEMASARAN DAN SOCIAL PRENEUR ERA DIGITAL SOCIETY 5.0 - Manap, Abdul; Hawari, Yusmita; Ginting, Riah Ukur Br; Saepullah, Asep; Sekianti, Atik; Sasmiyati, Rini Yulia; Edy, Norman; Pujadi, Arko; Buana, Lilik Swarnata Angga; Pujiningsih, Diana (Nindikayla Institute, 2023)
This community service aims to provide training and assistance in terms of making promotional facilities on social media for MSMEs in Ciledug District, Tangerang Regency. The chosen social media is Instagram, because for WhatsApp, on average, the trainees have already promoted there, so Instagram is an additional promotional media for them. There were 70 participants consisting of students and colleges with various businesses. They are very enthusiastic about participating in the training, because they are guided from the beginning of making Instagram and the others social media to uploading their products